2023
DOI: 10.3390/md21030141
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Parkinson Effects of Holothuria leucospilota-Derived Palmitic Acid in Caenorhabditis elegans Model of Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disease which is still incurable. Sea cucumber-derived compounds have been reported to be promising candidate drugs for treating age-related neurological disorders. The present study evaluated the beneficial effects of the Holothuria leucospilota (H. leucospilota)-derived compound 3 isolated from ethyl acetate fraction (HLEA-P3) using Caenorhabditis elegans PD models. HLEA-P3 (1 to 50 µg/mL) restored the viability of dopaminergic neurons. Sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
(75 reference statements)
0
5
0
Order By: Relevance
“…The mutant C. elegans strain NL5901 expresses the human α -synuclein gene in its body wall cells, which is, among others, associated with Parkinsonʼs disease 38 , as overexpressed α -synuclein leads to the formation of Lewy bodies and dopaminergic neurodegeneration 39 . In NL5901, the human α -synuclein is fused to yellow fluorescent protein (YFP), enabling the visualization of α -synuclein aggregation under a fluorescence microscope 38 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mutant C. elegans strain NL5901 expresses the human α -synuclein gene in its body wall cells, which is, among others, associated with Parkinsonʼs disease 38 , as overexpressed α -synuclein leads to the formation of Lewy bodies and dopaminergic neurodegeneration 39 . In NL5901, the human α -synuclein is fused to yellow fluorescent protein (YFP), enabling the visualization of α -synuclein aggregation under a fluorescence microscope 38 .…”
Section: Resultsmentioning
confidence: 99%
“…This results in a rapid and reproducible paralysis [36], which lacks the formation of Aβ deposits [37] but allows for the assignment of effects to Aβ toxicity while excluding life span effects, which is hardly possible using CL2006 [36]. The mutant C. elegans strain NL5901 expresses the human α-synuclein gene in its body wall cells, which is, among others, associated with Parkinsonʼs disease [38], as overexpressed α-synuclein leads to the formation of Lewy bodies and dopaminergic neurodegeneration [39]. In NL5901, the human α-synuclein is fused to yellow fluorescent protein (YFP), enabling the visualization of α-synuclein aggregation under a fluorescence microscope [38].…”
Section: Original Papersmentioning
confidence: 99%
“…It was discovered through transcriptomic research that palmitic acid affected many signaling pathways, including lipid metabolism in neurons. On the other hand, excessive ingestion of palmitic acid has been linked to neurodegenerative conditions, such as Parkinson's disease [ 150 , 151 ]. To prevent harmful effects such as oxidative stress, PLA has a critical role in low levels of stress, which can activate the stress response pathway.…”
Section: Resultsmentioning
confidence: 99%
“…There was a study reporting that PA inhibits the key molecules of the PI3K/AKT pathway to suppress the proliferation and metastasis of prostate cancer cells [51]. Recently, we found that Holothuria leucospilota-derived palmitic acid obtained from an ethyl acetate fraction was able to restore the viability of dopaminergic neurons and decrease α-synuclein aggregation, oxidative stress, and lipid accumulation, as well as extending the lifespan of a C. elegans model of Parkinson's disease [52]. Moreover, the PA obtained from the methanolic extract of Syzygium litoralle (Myrtaceae) showed antioxidant activity, with an IC50 value of 44.85 µg/mL [53].…”
Section: Discussionmentioning
confidence: 96%